A new route for the synthesis of phosphate esters: 2, 2′‐[benzene‐1, 2‐diylbis(oxy)]bis(5, 5‐dimethyl‐1, 3, 2‐dioxaphosphinane) 2, 2′‐dioxide. Issue 12 (1st December 2015) - Said, Musa A.; Ali, Adeeb Al‐Sheikh; Hughes, David L.
Abstract : Podand‐type ligands are an interesting class of acyclic ligands which can form host–guest complexes with many transition metals and can undergo conformational changes. Organic phosphates are components of many biological molecules. A new route for the synthesis of phosphate esters with a retained six‐membered ring has been used to prepare 2, 2′‐[benzene‐1, 2‐diylbis(oxy)]bis(5, 5‐dimethyl‐1, 3, 2‐dioxaphosphinane) 2, 2′‐dioxide, C6 H4 O[ cyclo ‐P(O)OCH2 CMe2 CH2 O]2 or C16 H24 O8 P2, (1), 2‐[(2′‐hydroxybiphenyl‐2‐yl)oxy]‐5, 5‐dimethyl‐1, 3, 2‐dioxaphosphinane 2‐oxide, [ cyclo ‐P(O)OCH2 CMe2 CH2 O](2, 2′‐OC6 H4 –C6 H4 OH), (2), and oxybis(5, 5‐dimethyl‐1, 3, 2‐dioxaphosphinane) 2, 2′‐dioxide, O[ cyclo ‐P(O)OCH2 CMe2 CH2 O]2, (3). Compound (1) is novel, whereas the results for compounds (2) and (3) have been reported previously, but we record here our results for compound (3), which we find are more precise and accurate than those currently reported in the literature. In (1), two cyclo ‐P(O)OCH2 CMe2 CH2 O groups are linked through a catechol group. The conformations about the two catechol O atoms are quite different, viz. one C—C—O—P torsion angle is −169.11 (11)° and indicates a trans arrangement, whereas the other C—C—O—P torsion angle is 92.48 (16)°, showing a gauche conformation. Both six‐membered POCCCO rings have good chair‐shape conformations. In both the trans and gauche conformations, the catechol O atoms are in the axial sites and the short P=O bonds are equatorially bound.